2020
DOI: 10.3390/foods9030259
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Marketing Factors Influencing Consumers’ Preferences and Acceptance of Organic Food Products—Recommendations for the Optimization of the Offer in a Developing Market

Abstract: Considering the benefits of the organic production system, it is recognized as one of the main drivers of future economic development. However, the imbalance between demand and supply at the local market level represents one of the serious obstacles that prevents its future growth. Therefore, this article examines the key factors related to the main elements of the offer that have the strongest impact on consumer preferences and acceptance of organic food products. In that sense, organic product, price, distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
12

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 48 publications
1
49
0
12
Order By: Relevance
“…Literature suggests that the majority of consumers have a positive attitude towards organic food, but few purchase it on a regular basis due to the price premium attached to it (Aertsens et al, 2009;Magnusson, 2004;Nguyen et al, 2019;Raza et al, 2019). Several studies (for instance, Marian et al, 2014;Melovic et al, 2020;Paul & Rana, 2012;Pawlewicz, 2020;Shafie & Rennie, 2012;Stolz et al, 2011) have observed that price premium is one of the main obstacles in the purchase of organic food, while the studies of (Aguilar & Vlosky, 2007;Dipeolu et al, 2009;Govindasamy et al, 2006;Obayelu et al, 2014;Owusu & Owusu Anifori, 2013;Saphores et al, 2007) argued that consumers are willing to pay more for organic food to some extent.…”
Section: Willingness To Paymentioning
confidence: 99%
“…Literature suggests that the majority of consumers have a positive attitude towards organic food, but few purchase it on a regular basis due to the price premium attached to it (Aertsens et al, 2009;Magnusson, 2004;Nguyen et al, 2019;Raza et al, 2019). Several studies (for instance, Marian et al, 2014;Melovic et al, 2020;Paul & Rana, 2012;Pawlewicz, 2020;Shafie & Rennie, 2012;Stolz et al, 2011) have observed that price premium is one of the main obstacles in the purchase of organic food, while the studies of (Aguilar & Vlosky, 2007;Dipeolu et al, 2009;Govindasamy et al, 2006;Obayelu et al, 2014;Owusu & Owusu Anifori, 2013;Saphores et al, 2007) argued that consumers are willing to pay more for organic food to some extent.…”
Section: Willingness To Paymentioning
confidence: 99%
“…Under the same conditions of soil, slope, and vegetation cover, Avanzi [86] reported that a more concave slope could concentrate the runoff flow leading to a greater erosion rate. These changes can significantly affect the further purpose and use of land, especially in the future agricultural and overall economic development [87].…”
Section: Discussionmentioning
confidence: 99%
“…Guzy [5] found that 94% of public is aware about the organic food but lack of interest is developed due to non lebling and high price. Melovic et al [10] analyse that price, food quality, distribution system and modern media as a promotional tool is the best factor to impact on consumer buying behaviour, Muttalageri and Mokshapathy [11] explored that in the Balgavi district that there is lack of govt. support for farmer consumers are not getting enough organic food in market, another factor is premium price of the product is also a factory for low market growth and less active behaviour of consumers.…”
Section: Literature Reviewmentioning
confidence: 99%